Singing the Law: The Musicality of Legal Performance - Sean Mulcahy (Law Text Culture, 2020)
What would the law sound like if it was sung? Whilst scholars have explored the relation between music and law, focus on the acoustic and musical dimensions of legal speech is relatively new. Exploring musical adaptations and remixes of legal transcripts, the paper argues that there is a latent musicality to legal speech. Using as case studies Opera Australia’s production of ‘Lindy’ and Donmar Warehouse’s production of ‘Committee’, where legal speech was adapted verbatim from legal transcripts into musical score, the paper investigates what these composers have to say about their jurisprudential source material. Through advancing this notion of latent musicality within legal speech, this paper suggests that legal speech works best when it appeals to its audience in the way that music appeals to its listener in terms of rhythm, pitch, and tone.